Estimated economic impact of pre‐filled ephedrine syringes in the operating room. Issue 7 (3rd March 2016) - Armoiry, X.; Carry, P.‐Y.; Lehot, J.‐J.; Michel, C.; Aulagner, G.; Piriou, V.
Abstract : Background: Syringes of ephedrine are usually prepared ahead of time in order to reduce the time to injection. Commercial pre‐filled syringes of ephedrine have been introduced to minimize the amount of waste. Our primary objective was to determine the economic impact of commercial syringes. We hypothesized that costs could be reduced compared to standard syringes. Methods: Using data extracted from our medical records system, we retrospectively measured the total dose of ephedrine received per patient in 2013 to estimate the number of administered standard syringes. The proportion of administered standard syringes was calculated as the total number of administered standard syringes divided by the number of delivered ampoules in 2013. Thereafter, we calculated the annual cost difference as the difference between the cost for commercial syringes and the cost for standard syringes. Endpoints were calculated overall and for each operating room. Results: At least one dose of ephedrine was given in 19, 422 patients (44, 943 administrations). The overall proportion of administered standard syringes was estimated to 52.8%. The threshold proportion of administered standard syringes for which commercial syringes would add no extra cost was 20.4%. In 30/32 operating rooms, the proportion of administered standard syringes was higher than 20.4%. The overall cost increase with commercial syringes was estimated to 51, 567 €. Among operating rooms, incremental costs varied between −703 and 5086 €. Conclusion: Based on our findings, pre‐filled ephedrine commercial syringes do not appear to reduce costs.